Propozycja narzędzia do pomiaru natężenia poczucia zagrożenia stereotypem wśród dzieci, opracowanego na podstawie koncepcji multizagrożeń Jenessy Shapiro i Stevena Neuberga - Borsich, Szymon; Deptuła, Maria (Studia Edukacyjne, 2018)
Scientificmagazines have published hundreds of research papers on stereotype threat. They indicated that despite their intellectual potential some individuals may experience lower performance in school tasks because of the fear of confirminga stereotype about the low abilities of their social group. Most of the research was of an experimental nature, with the use of a single manipulation within the experiment group and comparing its results to those of the control group. Additionally, despite two decades of research, discrepancies in how the term is definedor in the manipulation and measurement methods persist. The article outlines the development of a tool for measuring the intensity of a sense of low abilities stereotype threat among elementary school pupils (grades IV-VI) and the results of a pilot study. The scale was developed based on the theoretical assumptions of Shapiro’s and Neuberg’s multi-threat concept, which appears to put in order the aforementioned discrepancies in understanding the phenomenon’s essence and the ways it is measured.